Treatment Outcome of Pulmonary Tuberculosis Patients in Public Health Center - Arisandi, Desto; Nurlaili Farida Muhajir; Arum Nuryati (Poltekkes Kemenkes Kupang, 2025)
Background: Tuberculosis (TB) remains a contagious disease with high mortality rates worldwide, especially in developing countries like Indonesia, which is the second-largest contributor to TB cases after India. Objective: Analysis of factors associated with treatment outcome in pulmonary TB patients in public health centers at Gunungkidul Regency, D.I. Yogyakarta. Methods: An observational analytic study with a cross-sectional design was conducted on pulmonary TB patients in 30 public health centers, Gunungkidul Regency in 2020-2021. Inclusion criteria were age ≥15 years, and exclusion criteria were extrapulmonary TB patients and those who loss to follow-up the end of treatment. Secondary data were obtained from the Tuberculosis Information System TB 03 (SITB) of the Gunungkidul District Health Office. The research data were analyzed using chi-square test (bivariate) and logistic regression (multivariate). Results: A total of 272 pulmonary TB patients in 2020-2021, with the majority aged 45-54 years (22.8%), male (57%), new treatment category (96.3%), BTA/TCM positive (58.1%), had a history of DM (8.1%), and HIV positive status (0.8%). Logistic regression analysis showed that age (p<0.001) and bacteriological examination results (p=0.012) were significantly associated with treatment outcomes. However, gender, history of TB treatment, history of DM, and HIV status were not associated with treatment success. Conclusion: Age and bacteriological examination results (AFB/Xpert MTB) at the start of treatment contributed to the treatment success rate in pulmonary TB patients.